2010
DOI: 10.1021/ef901325e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Ultra-thin Molybdenum Trioxide Layer and Illumination Intensity on the Performance of Organic Photovoltaic Devices

Abstract: The effect of an ultra-thin molybdenum trioxide (MoO 3 ) layer thickness inserted between the indium tin oxide (ITO) substrate and copper phthalocyanine (CuPc) layer on the performance of organic photovoltaic devices (OPVs) was studied. Experimental results demonstrate that the short-circuit current density (J sc ) was decreased slightly with the increase of MoO 3 thickness; meanwhile, the fill factor (FF) was increased from 53.5 to 57.7%, respectively, leading to the improved power conversion efficiency with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…For this purpose, different inorganic layers were proposed such as ultrathin gold film or transition‐metal oxide . Among the transition‐metal oxides, MoO 3 was shown to be a very suitable ABL . Actually, MoO 3 is very efficient in optimizing the hole extraction due to its high work function that allows a good agreement with the HOMO value of the ED.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, different inorganic layers were proposed such as ultrathin gold film or transition‐metal oxide . Among the transition‐metal oxides, MoO 3 was shown to be a very suitable ABL . Actually, MoO 3 is very efficient in optimizing the hole extraction due to its high work function that allows a good agreement with the HOMO value of the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have shown that the introduction between the anode, which is usually an ITO film, and the organic electron donor, of a buffer layer [anode buffer layer (ABL)] produces significant improvement in the OPVCs performances 5. For instance, it has been shown that a MoO 3 3–10 or NiO 11–15 thin film is very efficient to improve the device performances and stability. However, even though the MoO 3 is n‐type 16, NiO is p‐type 15, nevertheless both buffer layers are efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cell performance of OPVs was sharply increased up to 8-12% with changing the various parameters (open circuit voltage (V oc ), current density (J sc ), fill factor (FF) and resistance, etc.) (Park et al, 2010;Zhang et al, 2010;Li et al, 2012;Kim et al, 2013Kim et al, , 2014. In order to get the high PCE of OPVs, it is important to decrease the resistance between the buffer layer and active layer because http://dx.doi.org/10.1016/j.solener.2015.07.047 0038-092X/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%